Achieving development and mitigation objectives through a decarbonization development pathway in South Africa. (20th June 2016) - Altieri, Katye E.; Trollip, Hilton; Caetano, Tara; Hughes, Alison; Merven, Bruno; Winkler, Harald
Abstract : Achieving the international 2 °C limit climate policy requires stringent reductions in GHG emissions by mid-century, with some countries simultaneously facing development-related challenges. South Africa is a middle-income developing country with high rates of unemployment and high levels of poverty, as well as an emissions-intensive economy. South Africa takes into account an assessment of what a fair contribution to reducing global emissions might be, and is committed to a 'peak, plateau and decline' emissions trajectory with absolute emissions specified for 2025 and 2030, while noting the need to address development imperatives. This work utilizes an economy-wide computable general equilibrium model (e-SAGE) linked to an energy-system optimization model (TIMES) to explore improving development metrics within a 14 GtCO2 e cumulative energy sector carbon constraint through to 2050 for South Africa. The electricity sector decarbonizes by retiring coal-fired power plants or replacing with concentrated solar power, solar photovoltaics and wind generation. Industry and tertiary-sector growth remains strong throughout the time period, with reduced energy intensity via fuel-switching and efficiency improvements. From 2010 to 2050, the model results in the unemployment rate decreasing from 25% to 12%, and the percentage of people living below the poverty line decreasing from 49% to 18%. Total energy GHG emissions were reduced by 39% and per capita emissions decreased by 62%. Policy relevance Lower poverty and inequality are goals that cannot be subordinated to lower GHG emissions. Policy documents in South Africa outline objectives such as reducing poverty and inequality with a key focus on education and employment. In its climate policy and Intended Nationally Determined Contribution (INDC), South Africa is committed to a peak, plateau and decline GHG emissions trajectory. As in many developing countries, these policy goals require major transformations in the energy system while simultaneously increasing affordable access to safe and convenient energy services for those living in energy poverty. The modelled scenario in this work focuses on employment and poverty reduction under a carbon constraint, a novel combination with results that can provide information for a holistic climate and development policy framework. This study has focused on the long term, which is important in generating clear policy signals for the necessary large-scale investments.